Relationship between Scrotal Biometry and Seminal Attributes in Berari Bucks - Patil, Manjusha G.; Ingawale, Maheshkumar V.; Hase, Pankaj B.; Kuralkar, Shailendra V.; Sawant, Sujata S. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Berari goat is the heritage and one of the potential animal genetic resources of Vidarbha region of Maharashtra. The present experimentestimated semen characteristics and their relationships with scrotal circumference in Berari bucks. The means of scrotal circumference,testicular length, and testicular width were 24.62 ± 0.51, 7.67 ± 0.30 and 5.04 ± 0.23 cm, respectively, with significant variations amongthe bucks. All the three traits were highly significantly and positively interrelated (r= 0.812 to 0.861), and had positive associations withmost seminal attributes (r= 0.176 to 0.581), except pH. Scrotal circumference of bucks significantly affected all the semen characteristics,except seminal pH. Sperm concentration is the important semen trait of Berari goat where reasonable genetic progress may be possiblethrough selection. The study demonstrated that the selection for increased scrotal circumference should have a favorable correlatedresponse in semen characteristics of Berari bucks.